The incidence of yellow rust and the industrial quality of the grain and the dough in bread wheat - Martínez-Cruz, Eliel; Buendía-Ayala, Blanca Lidia; Villaseñor Mir, Héctor Eduardo; Santa Rosa, René Hortelano; Espitia-Rangel, Eduardo; Buendía-González, María Ofelia (Revista Mexicana de Ciencias Agrícolas, 2019)
Incidence of wheat yellow rust affects physical quality of the grain, as well as that of flour and dough. The objective of this research was to evaluate the effect of stripe rust on the physical quality of grain and the mass depending on the presence and absence of the disease in bread wheat genotypes. The genotypes were sown under temporally in an experimental design of randomized blocks with two replications in an arrangement of split plots, treatments of with and without fungicide were assigned to large plots and varieties to small plots. The incidence of yellow rust was natural and used fungicide Folicur®. Severity of yellow rust was evaluated under field conditions. While quality traits such as laboratory evaluated the physical quality: the percentage of grains full and suck, its length and width, the weight of thousand grains and test weight, as well as grain hardness, flour yield, protein in flour, sedimentation volume and kneading time, were evaluated under laboratory conditions. Analysis of variance, Pearson correlations and mean comparison with Tukey test were performed. Yellow rust reduced physical quality of the grain and also flour yield. Genotypes with severity lower than 20% of yellow rust with and without the application of the fungicide showed small lost in percentage of filled grains, thousand kernel weight, test weight and flour yield. While in the majority of the genotypes the flour protein and evaluated dough variables showed no difference with and without the presence of the disease. So the use of yellow rust-tolerant genotypes renders better physical quality of the grain, but not with the flour and dough quality.
Keywords: bread wheat; physical quality of the grain; quality of the dough; yellow rust